Balloon Mitral Valvuloplasty (BMV) in Pregnancy: A Four-Year Experience at Shahid Gangalal National Heart Centre (SGNHC), Nepal - Regmi, Shyam Raj; Maskey, Arun; Dubey, Laxman; Bhatt, Yadav; Malla, Rabi; Sharma, Deewakar; Rajbhandari, Rajib; Limbu, Yuba Raj; KC, Man Bahadur (Nepalese Heart Journal, 2017)
Balloon Mitral Valvuloplasty (BMV) has been performed safely during pregnancy with good results. This study was intended to see the efficacy and safety of BMW in this subset. Retrospective analysis of 22 pregnant women among a total of 861 patients who had undergone BMV for severe mitral stenosis at SGNHC from January 2003 to December 2007 were done. Mean fulroscopy time was 7.5±4.8 min. post-BMV, the mean left atrial pressure dropped from 28.12±4.3 mmHg to 15.32±6.4 mmHg. Mitral valve area as assessed by echocardiography increased from 0.76 01770.21 cm2 to 1.8±0.26 cm2. all the patients showed symptomatic improvement. Six patients had an increase in MR by 2 grades. Twenty patients had a normal delevery while 2 underwent a caesarean section. There was no meternal morbidity or mortality in the peripartum period. On follow up for 26±15 months, all babies maintained normal growth and development without any thyroid disease or malignancy. During pregnancy BMV is feasible, safe and effective. Maternal and fetal outcomes are excellent. Growth and milestone of development are not affected.